Stereoselective nucleophilic addition of PhSCF2SiMe3 to chiral cyclic nitrones: Asymmetric synthesis of gem-difluoromethylenated polyhydroxypyrrolizidines and -indolizidines - Korkit Korvorapun (2018)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Fluoride-catalyzed nucleophilic addition of a difluoro(phenylsulfanyl)methyl group ("PhSCF2") generated from PhSCF2SiMe3 to nitrones was accomplished in satisfactory yields. High diastereoselectivities were observed with chiral polyoxygenated cyclic nitrones to provide the corresponding adducts, which were further manipulated to afford gem-difluoromethylenated polyhydroxypyrrolizidines and -indolizidines.